Tunable Colossal Anomalous Hall Conductivity in Half-Metallic Material Induced by d-Wave-Like Spin-Orbit Gap - Choi, Joonyoung; Park, Jin Hong; Kyung, Wonshik; Kim, Younsik; Kim, Mi Kyung; Kwon, Junyoung; Kim, Changyoung; Rhim, Jun Won; Park, Se Young; Jo, Younjung (Advanced Science, 2024)
The anomalous Hall conductivity (AHC) in magnetic materials, resulting from inverted band topology, has emerged as a key adjustable function in spin-torque devices and advanced magnetic sensors. Among systems with near-half-metallicity and broken time-reversal symmetry, cobalt disulfide (CoS2) has proven to be a material capable of significantly enhancing its AHC. In this study, the AHC of CoS2 is empirically assessed by manipulating the chemical potential through Fe- (hole) and Ni- (electron) doping. The primary mechanism underlying the colossal AHC is identified through the application of density functional theory and tight-binding analyses. The main source of this substantial AHC is traced to four spin-polarized massive Dirac dispersions in the kz = 0 plane of the Brillouin zone, located slightly below the Fermi level. In Co0.95Fe0.05S2, the AHC, which is directly proportional to the momentum-space integral of the Berry curvature (BC), reached a record-breaking value of 2507 Ω−1cm−1. This is because the BCs of the four Dirac dispersions all exhibit the same sign, a consequence of the d-wave-like spin-orbit coupling among spin-polarized eg orbitals.
Keywords: Anomalous hall effects; Berry curvature; Half metals; Half-metallic materials; Half-metallicity; Hall conductivity; Spin orbits; Spin torque; Spin-polarized; Tunables; anomalous hall effect; berry curvature; half-metals